Hypnobirthing Significantly Reduces Labor Pain in Indonesia: Hypnobirthing Secara Signifikan Mengurangi Nyeri Persalinan di Indonesia - Hayatun Nufus; Hesty Widowati; Rafhani Rosyid; Paramitha Amelia (Academia Open, 2024)
Hypnobirthing, a self-hypnosis practice aiding natural childbirth, lacks sufficient empirical evidence on its efficacy in mitigating labor pain, particularly during active phase I. This quasi-experimental study assessed hypnobirthing's effectiveness using a pretest-posttest non-equivalent control group design with 30 primi delivery mothers. Results indicated a significant reduction in pain levels (p = 0.000) among the hypnobirthing group compared to controls, emphasizing its potential as a non-pharmacological pain management tool. Integrating hypnobirthing into midwifery practice could enhance birthing experiences and mitigate risks associated with pathological labor, suggesting avenues for further research into its broader applicability and long-term effects. Highlight: Significant Pain Reduction: Hypnobirthing reduces active phase I labor pain significantly. Non-Pharmacological Tool: Effective alternative to pharmacological pain management during childbirth. Midwifery Practice: Enhances birthing experiences and reduces future pregnancy complications. Keywoard: Hypnobirthing, labor pain, active phase, quasi-experimental, midwifery